Interactive three‐dimensional virtual environment to reduce the public speaking anxiety levels of novice software engineers. Issue 2 (1st April 2019) - Denizci Nazligul, M.; Yilmaz, M.; Gulec, U.; Yilmaz, A.E.; Isler, V.; O'Connor, R.V.; Gozcu, M.A.; Clarke, P.
Abstract : Software engineering is a set of activities that rely not only on the technical tasks but also require abilities focused on social duties such as daily meetings and product introduction presentations. However, engineers may experience elevated levels of anxiety when required to present their work in an unfamiliar environment. More specifically, they may suffer from public speaking anxiety even though they are supposed to be effective in those social tasks as well as in their engineering activities. Fortunately, previous studies suggest that the virtual exposure intervention is an effective strategy to reduce public speaking anxiety. In this study, an interactive three‐dimensional virtual environment similar to real classrooms and auditoriums was developed to examine whether this might decrease the anxiety levels of novice software engineers. To compare the traditional and virtual exposure intervention, the sample set was divided equally into two groups including one experimental group and one control group. For 4 weeks, the virtual exposure intervention was conducted in the experimental group, whereas the cognitive behaviour therapy‐based psychoeducation was used in the control group. The findings from authors' study illustrate that the virtual exposure intervention may represent an alternative solution to the traditional interventions for software engineers seeking to overcome public presentation anxiety.